Hermite–Hadamard type inequalities for F-convex function involving fractional integrals - Pshtiwan Othman Mohammed; Mehmet Zeki Sarikaya (Journal of Inequalities and Applications, 2018)
Abstract In this study, the family F and F-convex function are given with its properties. In view of this, we establish some new inequalities of Hermite–Hadamard type for differentiable function. Moreover, we establish some trapezoid type inequalities for functions whose second derivatives in absolute values are F-convex. We also show that through the notion of F-convex we can find some new Hermite–Hadamard type and trapezoid type inequalities for the Riemann–Liouville fractional integrals and classical integrals.